Communication strategy of the Communication and Informatics Department of Payakumbuh in disseminating Covid-19 information in March – August 2021 - Sabrina Rahma Utami; Pitoyo Pitoyo (The Indonesian Journal of Communication Studies, 2021)
The Covid-19 pandemic is a situation that requires proper handling so that it does not spread further. Dissemination of Covid-19 information is one of the steps taken by the communication and informatics department of Payakumbuh (Diskominfo) to increase public participation by providing knowledge and changing people's attitudes to be able to take steps to prevent Covid-19. This study aims to determine the form of communication strategy of The Communication and Informatics Department of Payakumbuh in disseminating information on Covid-19 with supporting factors and inhibiting factors in its implementation. This research uses a qualitative approach with constructivism paradigm. The theory used in this study is the theory of diffusion of innovation. Data collection techniques were carried out through in-depth and semi-structured interviews, as well as observation. The results of the study show that the form of communication strategy is the stages of compiling communicants or communication targets, messages in the dissemination of Covid-19 information, media selection, determining the frequency of information dissemination, the role of communicators, and public response to the dissemination of information on Covid-19. One of the supporting factors in the dissemination of Covid-19 information is that The Communication And Informatics Department Of Payakumbuh’s public relations officer has understood the use of information and communication technology, thus facilitating the dissemination of Covid-19 information through new media, and one of the inhibiting factors is the lack of coordination at The Communication and Informatics Department Of Payakumbuh in managing the website, and the unopenness of hospital management in Payakumbuh in providing information updates on Covid-19 in Payakumbuh City.